Are we alone? : philosophical implications of the discovery of extraterrestrial life - Davies, P. C. W. (New York : BasicBooks, 1995)
Considers what the discovery of extraterrestrial life would mean for science, religion, and beliefs about mankind.
A brief history of SETI -- Extraterrestrial microbes -- Alien message -- Against aliens -- The nature of consciousness -- Alien contact and religious experience -- Appendix 1 : Project Phoenix -- Appendix 2 : The argument for duplicate beings.
Includes bibliographical references (pages [151]-152) and index.
Keywords: Life on other planets; Life -- Origin; Cosmology